Implementasi Manajemen dalam Pengembangan Perpustakaan Sekolah di SMAN Kualuh Selatan Labuhanbatu Utara - Aprilia, Dinda; Harahap, Nursapia; Faishal, Muhammad (Al-DYAS, 2025)
This study aims to accurately describe how school management and library development are implemented at SMAN 1 Kualuh Selatan, with a focus on the library's role as part of the educational process. The research employs a descriptive qualitative method, collecting data through in-depth interviews, direct observations, and documentation. Information was gathered from various informants, including the principal, library managers, teachers, and students, to provide a deeper understanding of school and library management. For data analysis, this study follows the steps outlined by Miles and Huberman: data reduction, data display, and conclusion drawing. The findings indicate that management at SMAN 1 Kualuh Selatan focuses on human resource management, budgeting and financing, as well as facilities and infrastructure, including the library. It was found that the school’s human resources are well-managed, though there are challenges in library development that still require improvements, particularly in collection and staffing. Supporting factors for library development include stakeholder collaboration, literacy activities, and government policies, while the primary constraint is the limited number of professional staff. This study concludes that while significant efforts have been made in library development at SMAN 1 Kualuh Selatan, there is still a need for improvements in resource qualification and collection management to ensure the library can optimally support the school’s educational goals.